ТАРИЙХШЫ Р.ҚОСБЕРГЕНОВ ИЗЕРТЛЕЎЛЕРИНДЕ ҚАРАҚАЛПАҚ-РУС ҚАТНАСЫҚЛАРЫ МӘСЕЛЕСИ - Кощанов, Б.А.; Бекбаулиева, Н.Б. (FAN va JAMIYAT, 2025)
The article considers the life and scientific heritage of the Honored Scientist of Karakalpakstan, Doctor of Historical Sciences Rzambet Kosbergenov. The article reveals the enormous scientific significance of the monograph, the scientific novelty of the doctoral and candidate dissertation of the scientist, professor R. Kosbergenov in modern historical science.